Probing the magnetic polaron state in the ferromagnetic semiconductor HgCr2Se4 with muon-spin spectroscopy and resistance-fluctuation measurements - Mitschek, Merlin; Hicken, Thomas J.; Yang, Shuai; Wilson, Murray N.; Pratt, Francis L.; Wang, Chennan; Blundell, Stephen J.; Li, Zhilin; Li, Yongqing; Lancaster, Tom; Müller, Jens (Physical Review B, 2022)
Combined resistance noise and muon-spin relaxation (μSR) measurements of the ferromagnetic semiconductor HgCr2Se4 suggest a degree of magnetoelectric coupling and provide evidence for the existence of isolated magnetic polarons. These form at elevated temperatures and undergo a percolation transition with a drastic enhancement of the low-frequency 1/ f -type charge fluctuations at the insulator-to-metal transition at ∼95–98 K in the vicinity of the magnetic ordering temperature TC ∼ 105–107 K. Upon approaching the percolation threshold from above, the strikingly unusual dynamics of a distinct two-level fluctuator superimposed on the 1/ f noise can be described by a slowing down of the dynamics of a nanoscale magnetic cluster, a magnetic polaron, when taking into account an effective radius of the polaron depending on the spin correlation length. Coinciding temperature scales found in μSR and noise measurements suggest changes in the magnetic dynamics over a wide range of frequencies and are consistent with the existence of large polarized and domain-wall-like regions at low temperatures, that result from the freezing of spin dynamics at the magnetic polaron percolation transition.
EPrint Processing Status: Full text deposited in DRO